The effect of a combination of permanent breeding cage and low housing density on the reproductive success of farmed blue foxes - Pyykönen, Teija; Hänninen, Sari; Mohaibes, Maarit; Sepponen, Juhani; Mononen, Jaakko; Ahola, L. (Elsevier, 2008)
Social factors are known to affect the reproduction of many canids both in the wild and in farms. For example, reproduction in farmed silver foxes is regulated by social stress; foxes seem to benefit from noncramped housing conditions and permanent breeding cages. However, no comparable studies have been carried out in farmed blue foxes. The aim of our experiment was to create an alternative, improved, economically viable and practical housing solution for blue foxes. Therefore, we compared reproductive performance of blue foxes in permanent breeding cages with low animal densities (L group, N=79) and traditional housing with its changing social environment with high animal density (H group, N=74). The reproductive data from the L and H groups were compared separately for primiparous and multiparous vixens because the reproductive performance in primiparous vixens was substantially lower (P<0.001) than in multiparous vixens. Altogether, 41 and 39% of the primiparous vixens in the H and L group whelped (P>0.05), but only 28 and 34%, respectively, weaned at least one cub (P>0.05), i.e., 72 and 66% of the primiparous vixens did not reproduce in the H and L group, respectively (P>0.05). The total reproductive performance, expressed as cubs at weaning per breeding female, was 1.7+/-3.5 for the H and 1.6+/-2.9 for the L group (P>0.05). In the primiparous vixens, the only statistically significant difference observed between the two housing systems was that the onset of oestrus occurred five days earlier in the H than in the L group (P<0.05). All multiparous vixens in the L group exhibited oestrus compared to 94% in the H group (P>0.05). Furthermore, there was a nonsignificant (ns) trend for fewer barren females (9% versus 17%), more successfully reproducing vixens (83% versus 74%) and a higher number of live-born cubs (10.9+/-4.7 versus 9.4+/-3.9) in the L than in H group in the multiparous vixens (for all P>0.05). This resulted in 1.7 and 1.4 cubs more per breeding and per mated vixen, respectively, at weaning in the L group (7.3+/-5.0) compared to the H group (5.6+/-4.2), but also this difference was nonsignificant. Although our present results lack statistical significance, they are promising enough to encourage field experiments with sufficiently large number of animals to prove or disprove these preliminary findings that lower housing density and permanent breeding cage, together or separately, may enhance reproduction particularly in multiparous blue fox vixens.
Keywords: Ko; tiheys; sinikettu; turkiseläimet; pennut; eläinsuojat; lisääntyminen; jalostus; stressi; hyvinvointi; furbearing animals; animal housing; density; reproduction; breeding; stress; animal welfare; blue fox; cub losses; social relations